Techno-economic analysis of a low carbon back-up power system using chemical looping. (October 2020) - Diego, M.E.; Abanades, J.C.
Abstract: This work assesses the techno-economic viability of an innovative CO2 -free back-up power system. A novel chemical looping reactor is at the core of the process, where a pressurized air stream is heated up by the slow oxidation of a packed bed of reduced solids, before its expansion in a gas turbine to generate electricity. In this reactor, air flows through empty gas conducts with fully permeable non-selective perforated walls. Such gas conducts traverse the bed of solids longitudinally, so that the pressure drop is minimized. A diffusionally-controlled flow of oxygen is established through the gas permeable wall, which results in long oxidation times for the bed of reduced particles. A case example is described in this study, where a reactor that uses iron materials as oxygen carrier is designed to store renewable energy (an input of 1.4 MWth of biogas) on a weekly basis and release it to supply a maximum power peak of 57 MWth in the power discharge mode for more than 8 h. A packed bed reactor of 3.3 m I.D. and 50 m length is employed for this application, which is traversed by gas conducts of 0.04 m I.D., with 0.002 m wall thickness and a fraction of orifices in the wall of 0.12. A preliminary economic analysis of the novel system indicates that this low carbon configuration could be competitive against fossil fuel back-up alternatives in several scenarios, preferably with carbon prices exceeding 100€/t CO2 . Highlights: A back-up power system with low carbon footprint using a novel chemical looping reactor is analysed. The reactor allows the slow oxidation of the solids with a diffusional flow of O2 . A cost analysis shows the system can be competitive against the benchmark.